2020
DOI: 10.1080/17437199.2020.1728564
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of affective responses to acute high intensity interval exercise compared with continuous moderate- and high-Intensity exercise

Abstract: There is evidence for the physical health benefits of high intensity interval exercise (HIIE), but its public health potential has been challenged. It is purported that compared with moderate-intensity continuous exercise (MICE) the high intensity nature of HIIE may lead to negative affective responses. This systematic review (PROSPERO CRD42017058203) addressed this proposition and synthesised research that compares affective responses to HIIE with MICE and vigorous intensity continuous exercise (VICE), during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 90 publications
(209 reference statements)
4
60
0
1
Order By: Relevance
“…With a marked increase in the number of studies published in recent years, it is clear now that interval training can be perceived as equally or even more enjoyable than MICT when assessed acutely (Niven et al, 2020;Stork et al, 2017). Our results corroborate these findings since no differences were observed between SIT-T, SIT-WB, and MICT after the first training session.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…With a marked increase in the number of studies published in recent years, it is clear now that interval training can be perceived as equally or even more enjoyable than MICT when assessed acutely (Niven et al, 2020;Stork et al, 2017). Our results corroborate these findings since no differences were observed between SIT-T, SIT-WB, and MICT after the first training session.…”
Section: Discussionsupporting
confidence: 87%
“…As previously mentioned, training load was readjusted based on the results of the new incremental test after the eighth week of training. As recently highlighted by Niven et al (2020), a potential limitation on previous research is that MICT intensity has been typically considered based on HR or V O 2max percentages. Because these approaches do not accommodate individual differences in metabolism that may, otherwise influence affective responses and attitudes, we consider the use of an intensity based on VT 2 as a strength of our experimental design.…”
Section: Moderate-intensity Continuous Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…One plausible approach might be interval training, whereby the intensity of movement is intermittently varied. Studies have shown that interval training can improve enjoyment (Stork et al, 2017 ), affective response (Niven et al, in press ), and mental and physiological adaptations (Martland et al, 2020 ) in comparison to continuous moderate intensity exercise. Finally, enjoyment is an important factor mediating the level of PA adherence (Wankel, 1993 ; Jekauc, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research of affective responses to exercise has been guided by Russell's (1980) circumplex model of affect comprising the dimensions of valence and arousal; primarily studies have focused upon how pleasant versus unpleasant (i.e., valence) individuals perceive the experience of physical activity to be (e.g., Williams et al, 2012;Williams and Raynor, 2013). Over a period of 50 years of research, the widely promoted "feel good" effect of exercise has been scrutinized (Ekkekakis et al, 2011;Ekkekakis and Brand, 2019); further, popular claims extolling the virtues of high-intensity interval training related to the cliché "no pain, no gain" have been the focus of recent affect-related research (Stork et al, 2018;Niven et al, 2020;Roloff et al, 2020). Numerous studies highlight that affective states derived from exercise are not purely positive; rather, over the course of exercise, affective states vary, and typically shift between pleasant and unpleasant hedonic valence (Backhouse et al, 2007;Ekkekakis et al, 2008;Rose and Parfitt, 2012).…”
Section: Introductionmentioning
confidence: 99%